Local Service Provision in Selected OECD Countries : Do Decentralized Operations Work Better? - Ahmad, Ehtisham (IMF Working Papers; Working Paper ;, 2008)
There is a widespread presumption that decentralization improves public service provision. This has led to policy prescriptions that are assiduously adhered to by countries and international. This paper reviews the recent evidence from OECD countries-which is seen to be inconclusive. This suggests the need for a careful design of programs that take into account the political economy constraints and incentives, as well as more systematic and thorough evaluations of outcomes.